Potential of Solar PV Electrical Energy with a Capacity of 2x550 Wp on Cadet Training Ships - Amrillah, Muhamad Fahmi; Yulianto, Andri; Widjatmoko, Eko Nugroho; Yudha, Dimas Pratama; Firzatullah, R Muhammad (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2025)
The development of the utilization of electrical energy sourced from the sun is currently experiencing very rapid development. The use of electrical energy sourced from the sun is not only used for industrial generation, currently the transportation industry also utilizes electrical energy sourced from the sun for propulsion and domestic needs. This study discusses the potential of electrical energy that can be generated by solar PV with a capacity of 2x550 Wp which will be implemented on cadet training ships. Solar irradiance is the most important component for the process of generating electrical energy, where later the irradiance value will become electrical energy using solar PV media. The irradiance value is obtained from a web application called solarglobalatlas which already has big data about the irradiation value in various places. This study took irradiation values in the coordinates area -2.953161°, 104.886022° (-02°57'11